Moral and religious responses to the COVID-19 pandemic in Pakistan - Zehmisch, Philipp (CoronAsur, 2020)
Moral and religious responses to the COVID-19 pandemic in Pakistan contributed by Philipp Zehmisch, 14 August 2020 When the COVID-19 pandemic was rapidly spreading across the globe, Pakistan joined the global trend and declared a country-wide lockdown in mid-March. The lockdown inhibited major parts of the already struggling Pakistani economy from functioning in the typically … Moral and religious responses to the COVID-19 pandemic in Pakistan Read More
Gesehen am 17.02.2022